Neural network-based NARX models in non-linear adaptive control - Dzieliński, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The applicability of approximate NARX models of non-linear dynamic systems is discussed. The models are obtained by a new version of Fourier analysis-based neural network also described in the paper. This constitutes a reformulation of a known method in a recursive manner, i.e. adapted to account for incoming data on-line.
Keywords: neural networks; adaptive control; nonlinear systems